Pengembangan Sistem Informasi Pelayanan Publik Berbasis Web sebagai Upaya Digitalisasi Layanan di Kecamatan Gebog - Adisaputra, Rizky; Setiaji, Pratomo (Lembaga Yasin AlSys, 2025)
The lack of studies on the digitalization of public services at the sub-district level forms the background of this research, despite evidence that digitalization significantly improves service quality and efficiency. This study aims to design and implement a web-based public service information system in Gebog Sub-District. The approach used is Research and Development (R&D) with the waterfall model. Five respondents were purposively selected, consisting of three government officials and two local residents. Data were collected through observation, interviews, documentation, and user satisfaction questionnaires, and analyzed descriptively. The results show that the developed information system reduced service time from 2–3 days to just 1 day. The average user satisfaction score reached 4.44 out of 5, with ease of access receiving the highest rating, while data security was identified as an area needing improvement. The study concludes that the web-based information system is effective in enhancing the efficiency and quality of public services at the sub-district level. The implications highlight the need to strengthen internet infrastructure, improve digital literacy among officials and citizens, and develop more robust system security features. This study contributes empirical insights to the e-government literature at the local level and opens opportunities for further research with a broader and more diverse respondent base.